Characteristics of leachate from buried trash composed of disassembling imported electrical appliances and municipal refuse - FANG Cheng-ran; SHEN Dong-sheng; HE Ruo (浙江大学学报. 农业与生命科学版, 2002)
Solid wastes that remain after disassembling imported unusable electrical appliances constitute a serious pollution source of environment. Experiment on simulated acid rain leaching conditions of about 10-years rainfall showed the following results: When wastes were blended buried municipal in the leachate showed an initial marked increase. In the long run, however, the concentration of various pollutants in the collected leachate approached the pure municipal refuse, as that the amount of CODcr, oil, Cu, Pb, Ni and Hg in leachate did not exceed the limit of standard of discharge. Release of main pollutants in the leaching was generally in accord with the equation: Ct=C0tb.